PENGARUH KUALITAS LAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PELANGGAN - Silviana Fadilla Prasevie; Dr. Ismail Razak, M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of this study was to analize the impacts of service quality and customer value on the satisfaction of customers. Questionnaires are used to collect data from Boks Café customer in Bumiayu, Kabupaten Brebes, Central java by using scale of Likert. In this study, accident sampling method was used and data analysis method was simple linear regression and multiple linear regression. The results of this study indicated that service quality and customer value positively and significant influenced the satisfaction of customers. The conclution of this study is that customer value was dominant than service quality in influencing the satisfaction of customers.